Fungsi Direksi Bahasa: Kajian Tindak Tutur dalam Film Shalah Al-Din Al-Ayyu?bi Al-Bathl Al-Usthurah - Tuti Harianti; Maksum Maksum; Tafiati Tafiati (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This study discusses the directive speech acts in the animation movie ?al??udd?n: Al-Ba?hl Al-Us??rah. The object of this study is the types of directive speech acts. This study aimed at finding out the form of directive speech acts in episodes 12 and 13 of animation movie ?al??udd?n: Al-Ba?hl Al-Us??rah using the theories of Yule, Searle, and Wijana. This qualitative research applied observational methods. The data were collected using the listening and recording technique. The results of this study indicated that 122 directive speech acts were found. Based on the type of directive speech acts, 4: direct literal speech act, direct non-literal speech act, indirect literal speech act, indirect non-literal speech act. The result of the analysis found that there were 109 direct literal speech act expressions, 3 direct non-literal speech act expressions, 7 direct literal speech act expressions and 3 indirect non-literal speech act expressions.